Semantic Transformation In Cultural Heritage Study In The Semiotics Of The Mark - Mohammed Ameen, Maan Jassim; Mahmood Mashi, Rafid (Opción, 2019)
The signs of their cultural dimension have been acquired as facts subject to the society in its movement and development, and have varied according to the diversity of knowledge and human needs. There are words, signs, sym- bols, effects, gestures and scenes. Each system is characterized by semiotics with special signs. The signs can be classified according to their origin. Human behavior deliberately, there are natural sign sand artificial markers.The se- mantic transformation has many causes, which are influenced by the develop- ment of society and the change of culture. The symbolism is unstable and the semantic change can be described as an aspect of semantic evolution. It has been accompanied by a change in meaning and significance due to changes in societies as a result of evolution. Many researchers have tried to study the images of this change. , And the causes of the occurrence, as well as the various reasons that interfere with the semantic change of the mark, which is the de- velopment that occurs in society one of the important factors in the semantic transformation of signs and meanings. This research sought to reveal the most important factors of the transformation of semantic cultural heritage. The crescent was chosen as a model for detecting the transformation of se- mantics across different time periods of transformation and revealing the reasons for this transformation. The image of the crescent appeared in the ancient Iraqi sculptures as a symbol of the goddess of the moon Nana in the Sumerians or O, the name of the god of the moon in Babylon and Assyria and their guide and protector. And the appearance of the image of the moon in the ancient carvings as a symbol of the moon god,has become a sign of the crescent of Muslims and the image of the Cres- cent was associated with the beginning of the months of the Lunar year and associated with the image of the month of Ramadan. Cultural changes also apply to many of the cultural symbols and symbols transmitted by generations as part of their cultural heritage, whose semantic transforma- tions have been linked to intellectual and ideological transformations in the culture of societies.